2011
DOI: 10.1186/1471-2164-12-379
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing of a QTL-rich region of the Theobroma cacao genome using pooled BACs and the identification of trait specific candidate genes

Abstract: BackgroundBAC-based physical maps provide for sequencing across an entire genome or a selected sub-genomic region of biological interest. Such a region can be approached with next-generation whole-genome sequencing and assembly as if it were an independent small genome. Using the minimum tiling path as a guide, specific BAC clones representing the prioritized genomic interval are selected, pooled, and used to prepare a sequencing library.ResultsThis pooled BAC approach was taken to sequence and assemble a QTL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…and other diseases in cacao. Kuhn et al (2011) identified 19 COSII SNP markers that co-locate with existing QTLs in cacao, and that can be used for genotyping and off-typing in cacao breeding programs and for genetic mapping and studies to trace co-location of genes regulating important traits in cacao and other species. Feltus et al (2011) used a BAC-based physical map to identify candidate genes for bean shape, pod weight, and Black Pod resistance contained within QTL intervals.…”
Section: Molecular Approaches: Application Of Genomic Tools Gene Dismentioning
confidence: 99%
See 1 more Smart Citation
“…and other diseases in cacao. Kuhn et al (2011) identified 19 COSII SNP markers that co-locate with existing QTLs in cacao, and that can be used for genotyping and off-typing in cacao breeding programs and for genetic mapping and studies to trace co-location of genes regulating important traits in cacao and other species. Feltus et al (2011) used a BAC-based physical map to identify candidate genes for bean shape, pod weight, and Black Pod resistance contained within QTL intervals.…”
Section: Molecular Approaches: Application Of Genomic Tools Gene Dismentioning
confidence: 99%
“…Nevertheless, the future outlook for improved cacao planting material was deemed promising based on the ongoing research; conventional breeding and that involving genomic tools (Wilkinson, 2001;Figueira and Alemanno, 2005;Guiltinan, 2007;Guiltinan et al, 2008;Kuhn et al, 2011).…”
Section: Molecular Approaches: Application Of Genomic Tools Gene Dismentioning
confidence: 99%
“…This approach is the most straightforward for searching molecular resources functional in agriculture and ecology (Feltus et al . ; Henry ; Pootakham et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Rounsley et al (2009) sequenced and assembled a 19Mbp region of chromosome 3 in rice, using the 454 reads and was able to generate scaffolds with size ranging from 243 Kbp to 518 Kbp. Similar approaches have been used in cacao (Feltus et al, 2011) and Barley (Steuernagel et al, 2009). …”
Section: Genome Surveys and Partial Genome Assemblymentioning
confidence: 99%